The Influence of Marketing Mix on Fruit Purchasing Decisions (Case Study: Hokky Buah Panglima Sudirman) - Finurih, Prayoga Eka; Nurhadi, Eko; Roidah, Ida Syamsu (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This study aims to analyze the effect of the 4P marketing mix (Product, Price, Promotion, Place) on fruit purchasing decisions at Hokky Panglima Sudirman Minimarket. This research is motivated by the high productivity of horticultural fruits, the lack of public interest in fruit consumption, and the intense competition faced by Hokky Buah Panglima Sudirman Minimarket. The research sample of 100 respondents was analyzed using the SEM-PLS method. The results showed that: Product, Price, and Promotion have a significant influence on Purchasing Decisions at the 5% Alpha level; Place has a significant influence on Purchasing Decisions at the 10% Alpha level. This research contributes to knowledge about the influence of the 4P marketing mix on fruit purchasing decisions at minimarkets. The results of this study can help Minimarket Hokky Panglima Sudirman in improving its marketing strategy to increase sales of fruit products.